CRYSTAL STRUCTURE OF N-(NAPHTHALENE- 1-YL)-P,P-DIPHENYLPHOSPHINOTHIOIC AMIDE - Harbi Tomah Al-Masri; Ziad Moussa (European Scientific Journal, ESJ, 2014)
Refluxing of the C10H7-1-HNPPh2 with elemental sulfur in toluene (1:1 molar ratio) afforded C10H7-1-HNP(S)Ph2 (1). The crystal structure of 1 has been characterized by single X-ray diffraction method. 1 crystallized in the triclinic space group P-1, a = 9.986(5) Å, b = 10.306(5) Å, c = 10.837(5) Å, α = 66.350(5)°, β = 72.961(5)°, γ= 67.828(5)°, Z = 2. The structure was solved by direct methods, and refined by full-matrix least squares techniques to an R factor of 0.015 for 3538 observed reflections. In the crystal the Patom showed a distorted tetrahedral environment.